Determinan Market Share Bank Umum Syariah di Indonesia - Sindi Ali; Hendra H. Dukalang; Rifadli D. Kadir (Department of Islamic Banking, 2022)
This study aims to determine whether CAR, ROA, NPF, FDR affect the Market Share of Islamic Commercial Banks in Indonesia for the 2017-2021 period. This study uses Panel Data analysis. The results of this study conclude (1) Capital adequacy ratio (CAR) has a negative and insignificant effect on the market share of Islamic banking in Indonesia; (2) Return on assets (ROA) has a positive and insignificant effect on the market share of Islamic banking in Indonesia; (3) Non-performing financing (NPF) has a negative and significant effect on the market share of Islamic banking in Indonesia; (4) Financing to deposit ratio (FDR) has a negative and insignificant effect on the market share of Islamic banking in Indonesia and (5) CAR, ROA, NPF and FDR together have an effect on the market share of Islamic commercial banks in Indonesia. Penelitian ini bertujuan untuk mengetahui apakah CAR, ROA, NPF, FDR berpengaruh terhadap Market Share Bank Umum Syariah di Indonesia periode 2017-2021. Penelitian ini menggunakan analisis data panel. Hasil penelitian ini menyimpulkan (1) Capital adequacy ratio (CAR) berpengaruh negative dan tidak signifikan terhadap market share perbankan syariah di Indonesia; (2) Return on assets (ROA) berpengaruh positif dan tidak signifikan terhadap market share perbankan syariah di Indonesia; (3) Non performing financing (NPF) berpengaruh negative dan signifikan terhadap market share perbankan syariah di Indonesia; (4) Financing to deposit ratio (FDR) berpengaruh negative dan tidak signifikan terhadap market share perbankan syariah di Indonesia dan (5) CAR, ROA, NPF dan FDR secara bersama-sama berpengaruh terhadap market share bank umum syariah di Indonesia